Interventional Radiology Management of Vascular Complications From Gastrointestinal Interventions. (15th February 2023) - Narayanan, Harish A.; Naidu, Sailendra G.; Alzubaidi, Sadeer; Patel, Indravadan; Staack, Sasha; Oklu, Rahmi
Abstract : Recent advances in gastrointestinal interventions have led to the development of percutaneous and endoscopic procedures that can be performed in minimally invasive manner as an alternate to invasive surgery. Although the vast majority of these procedures have successful outcomes, there are potential complications. The diagnosis of these complications is often elusive. Interventional radiology can offer minimally invasive management of such complications. This educational activity aims to illustrate this through a review of several cases encountered at our institution.